Analisis Penerapan Akuntansi Dalam Penyajian Laporan Keuangan Pada Perkumpulan Divisi Perempuan Tim Relawan Untuk Kemanusiaan (TRUK) - Novita Anggraini; Wilhelmina Mitan; Pipiet Niken Aurelia (Universitas 45 Surabaya, 2023)
This study aims to determine the application of accounting in the presentation of financial reports at the Association of Women's Division Team Volunteers for Humanity (TRUK) based on financial accounting standards, namely ISAK 35. The method used in this research is descriptive qualitative with data sources in the form of primary data and secondary data. Data collection techniques in the form of observation, interviews and documentation using qualitative descriptive data analysis techniques. The results of the study show that the Association of Women's Division Team Volunteers for Humanity (TRUK) has presented financial statements consisting of a statement of financial position, profit and loss statement and cash report. Based on the financial accounting standards for non-profit entities in presenting financial statements, the Association of Women's Division Team Volunteers for Humanity (TRUK) has not presented financial statements based on ISAK 35 because it still uses the format for presentation of financial reports prepared by donating organizations.